2021
DOI: 10.1214/20-aos1963
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry helps: Eigenvalue and eigenvector analyses of asymmetrically perturbed low-rank matrices

Abstract: This paper is concerned with the interplay between statistical asymmetry and spectral methods. Suppose we are interested in estimating a rank-1 and symmetric matrix M ∈ R n×n , yet only a randomly perturbed version M is observed. The noise matrix M − M is composed of independent (but not necessarily homoscedastic) entries and is, therefore, not symmetric in general. This might arise if, for example, when we have two independent samples for each entry of M and arrange them in an asymmetric fashion. The aim is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Further, entrywise statistical analysis has recently received significant attention for various statistical problems [4,5,23,24,27,30,42,45,74,82,90,97,108,115]. For instance, entrywise guarantees for spectral methods are obtained in [27,42] based on an algebraic Neumann trick, while the results in [4,30,115] were established based on a leave-one-out analysis. The work by [27,69,70] went one step further by controlling an arbitrary linear form of the eigenvectors or singular vectors of interest.…”
Section: Further Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, entrywise statistical analysis has recently received significant attention for various statistical problems [4,5,23,24,27,30,42,45,74,82,90,97,108,115]. For instance, entrywise guarantees for spectral methods are obtained in [27,42] based on an algebraic Neumann trick, while the results in [4,30,115] were established based on a leave-one-out analysis. The work by [27,69,70] went one step further by controlling an arbitrary linear form of the eigenvectors or singular vectors of interest.…”
Section: Further Related Workmentioning
confidence: 99%
“…For instance, entrywise guarantees for spectral methods are obtained in [27,42] based on an algebraic Neumann trick, while the results in [4,30,115] were established based on a leave-one-out analysis. The work by [27,69,70] went one step further by controlling an arbitrary linear form of the eigenvectors or singular vectors of interest. These results, however, typically lead to suboptimal performance guarantees when the row dimension and the column dimension of the matrix are substantially different.…”
Section: Further Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A glimpse of our approach and our contributions a) Eigen-decomposition meets statistical asymmetry: The current paper makes progress in a setting where the noise matrix H consists of independent (but possibly heterogeneous and heteroscedastic) zero-mean components. Our approach is inspired by the findings of [17]. Consider, for example, the case when H is a random and asymmetric matrix and when M is a rank-1 symmetric matrix.…”
Section: A Motivation and Challengesmentioning
confidence: 99%
“…As a result, a much larger than regular sample size requirement is necessary to tradeoff the estimation error of the expected projection distance. Most recently, Chen et al (2018) revealed an interesting phenomenon of the perturbation of eigenvalues and eigenvectors of such non-asymmetric random perturbations, showing that the perturbation of eigen structures is much smaller than the singular structures. In addition, some non-asymptotic perturbation bounds of empirical singular vectors can be found in Koltchinskii and Xia (2016), Bloemendal et al (2016) and Abbe et al (2017).…”
Section: Introductionmentioning
confidence: 99%